Program Pemberdayaan Ekonomi Keluarga Dhuafa Ibu Citra Warga Sawangan Depok Melalui Pengembangan Usaha Takoyaki - Salma Julia Imbarsyah; Salsa Silva Zahra; Riska Nabilah; Mulkan Habibi (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Dhuafa families are a group of families or communities with weaknesses in the economic sector so they must be helped. This group struggles hard every day against the poverty that plagues their lives and suffers increasingly severe economic impacts due to the high prices of basic commodities to meet their basic needs. Based on the analysis result, Ms. Citra, a resident of Sawangan Depok, is one of the poor groups who must be given attention and assistance. This service activity in the form of empowerment aims to improve the skills of poor families so that they can take better advantage of business opportunities through Takoyaki Business Development. By improving these skills, it is hoped that they can improve their economy by the problems they face and provide the support needed so that poor families can be financially independent and run businesses sustainably. This service method is carried out in several stages, starting with observing the condition of poor families, planning a program for empowering poor families, conducting a fundraising program, providing business capital assistance, and coaching poor families. This community service program show that empowerment activities help the poor family of Mrs. Citra, a resident of Sawangan Depok. Through the development of the Takoyaki business, this poor family seeks to improve the economy of Mrs. Citra's family.